Assessment of an inducible gene expression system for the expression of the bacterial YoeB toxin in the microalgae Chlorella vulgaris - Chieng, Yeo Chew; Shetlee, Ng; Harikrishna, J. A; Cha, T. S (2014)
Over-expression of the YoeB toxin of the yefM-yoeB toxin-antitoxin system from the Gram-positive bacterium Streptococcus pneumoniae is lethal in Escherichia coli as well as its native host. In this study, we aim to assess an inducible gene expression system that was previously developed for use in plants, for the regulated expression of the yoeB toxin gene in the microalgae Chlorella vulgaris. The inducible gene expression system used is a two-component system comprising of an activator vector pMDC150 containing the chimeric XVE transcriptional activator under the control of the constitutive 35S promoter and a responder vector pMDC221 containing the yoeB-GFP fusion gene under the control of an XVE-responsive promoter. This system has been successfully used for the controlled expression of the bacterial yoeB toxin in Arabidopsis thaliana. Here, both activator and responder constructs were transformed into Chlorella vulgaris using Agrobacterium tumefaciens-mediated transformation. Six transgenic Chlorella lines were eventually selected from antibiotic-selective plates and subjected to PCR amplification to confirm the nuclear integration of the XVE and yoeBGFP fusion genes in the microalgae. Transgenic Chlorella cells were treated with 200 μM 17-β-estradiol to induce the expression of the yoeB-GFP fusion gene. Following induction, growth of the transgenic Chlorella was monitored and expression of the GFP gene determined under fluorescent microscopy. This is the first report of elucidating the expression of a bacterial toxin gene in microalgae using a two-component inducible gene expression system that was initially developed for plants. The success of this study would enable us to develop an antibiotic marker-free system for the selection of transgenic microalgae by using 17-β-estradiol as an inducer.